The Autofictional Approaches, Affordances, Forms - Effe, Alexandra; Lawlor, Hannie (Palgrave Studies in Life Writing,, 2022)
This open access book offers innovative and wide-ranging responses to the continuously flourishing literary phenomenon of autofiction. The book shows the insights that are gained in the shift from the genre descriptor to the adjective, and from a broad application of "the autofictional" as a theoretical lens and aesthetic strategy. In three sections on "Approaches," "Affordances," and "Forms," the volume proposes new theoretical approaches for the study of autofiction and the autofictional, offers fresh perspectives on many of the prominent authors in the discussion, draws them into a dialogue with autofictional practice from across the globe, and brings into view texts, forms, and media that have not traditionally been considered for their autofictional dimensions. The book, in sum, expands the parameters of research on autofiction to date to allow new voices and viewpoints to emerge.